IMPLEMENTATION OF THE SMALL AND MEDIUM INDUSTRY (IKM) PROGRAM IN EMPOWERING BUSINESS ACTORS AT THE DEPARTMENT OF COOPERATIVES, SMES, AND TRADE OF BARRU REGENCY - Andi Rachmat; Resky Nur Fadillah (Meraja journal, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal